2013
DOI: 10.1371/journal.pone.0074832
|View full text |Cite
|
Sign up to set email alerts
|

Food Addiction: Its Prevalence and Significant Association with Obesity in the General Population

Abstract: Background‘Food addiction’ shares a similar neurobiological and behavioral framework with substance addiction. However whether, and to what degree, ‘food addiction’ contributes to obesity in the general population is unknown.Objectivesto assess 1) the prevalence of ‘food addiction’ in the Newfoundland population; 2) if clinical symptom counts of ‘food addiction’ were significantly correlated with the body composition measurements; 3) if food addicts were significantly more obese than controls, and 4) if macron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
182
7
12

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(234 citation statements)
references
References 36 publications
25
182
7
12
Order By: Relevance
“…The prevalence we detected in this study is somewhat lower than that observed predominately among non-Hispanic whites. 2,6,7 However, the median YFAS symptom count in our study is similar to a prior study conducted among young adults.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The prevalence we detected in this study is somewhat lower than that observed predominately among non-Hispanic whites. 2,6,7 However, the median YFAS symptom count in our study is similar to a prior study conducted among young adults.…”
Section: Discussionsupporting
confidence: 86%
“…6 Based on this scale, the prevalence of food addiction has been reported in 11.4% of college students 6 and 6.7%-8.4% of middle-aged women. 2,7 However, these studies were conducted among predominately non-Hispanic whites and thus have limited generalizability. Moreover, the prevalence of food addiction among low-income reproductive-aged women is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Macronutrient intake was estimated as percent of total calorie intake from those data. Participants with food addiction had higher relative calorie intake from fat and protein, but not carbohydrates, as compared with those with no food addiction [41].…”
Section: Relationships With Other Eating-related Constructsmentioning
confidence: 89%
“…In the most recent study reviewed, 38% of a sample of obese adolescent inpatients at a weight loss clinic could be said to have a food addiction. Pedram et al [13] found that those cases 5.4% of cases who were obese showed an increasing trend towards a food addiction with higher body mass among 652 adults. Further, those food addicts consumed more calories from protein and fat compared with controls, and clinical counts of food addiction correlated positively with body composition measures when the entire sample was observed.…”
Section: Overviewmentioning
confidence: 99%